2020
DOI: 10.1155/2020/1817635
|View full text |Cite
|
Sign up to set email alerts
|

Preprotection of Tea Polysaccharides with Different Molecular Weights Can Reduce the Adhesion between Renal Epithelial Cells and Nano-Calcium Oxalate Crystals

Abstract: Crystal adhesion is an important link in the formation of kidney stones. This study investigated and compared the adhesion differences between nano-calcium oxalate monohydrate (COM) and human renal proximal tubule epithelial (HK-2) cells before and after treatment with tea polysaccharides (TPSs) TPS0, TPS1, TPS2, and TPS3 with molecular weights of 10.88, 8.16, 4.82, and 2.31 kDa, respectively. TPS treatment effectively reduced the damage of COM to HK-2 cells, thereby resulting in increased cell activity, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“… 50 , 51 The decreased CaOx crystal adhesion by down-regulating the expression levels of CD68 and CD44 can provide an novel pathway to inhibit CaOx deposition in kidneys. 52 The results warrant further investigation of the protective effect of succinate on kidney stones and modulation. 53 …”
Section: Discussionmentioning
confidence: 93%
“… 50 , 51 The decreased CaOx crystal adhesion by down-regulating the expression levels of CD68 and CD44 can provide an novel pathway to inhibit CaOx deposition in kidneys. 52 The results warrant further investigation of the protective effect of succinate on kidney stones and modulation. 53 …”
Section: Discussionmentioning
confidence: 93%
“…After HK-2 cells are damaged by 200 μ g/mL nano-COD crystals for 12 h, cell viability decreases from 100.00% ± 1.27% to 54.84% ± 0.85%, indicating that COD crystals have obvious damage to cells, and this damage was moderate, which was convenient to carry out the protection experiment of polysaccharide [ 14 , 43 ]. The five polysaccharides used three concentrations of 20, 40, and 80 μ g/mL to protect HK-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Plant polysaccharides can protect renal epithelial cells from oxidative damage by inhibiting the adhesion of CaOx crystals to cells. For example, Zhao et al [ 14 ] found that tea polysaccharides can effectively protect HK-2 cells from COM damage, thus increasing cell viability, restoring cell morphology, increasing lysosome integrity, and reducing crystal adhesion. These features inhibit the production of kidney stones.…”
Section: Introductionmentioning
confidence: 99%
“…For example, tea polysaccharides with different structural features were found to display different hypoglycemic activities in vitro ( 9 ). Zhao et al found that tea polysaccharides with different molecular weights ( M w) displayed different protective effects on cells and different inhibition abilities of crystal adhesion ( 12 ).…”
Section: Introductionmentioning
confidence: 99%